Strongly localized dark modes in binary discrete media with cubic-quintic nonlinearity within the anti-continuum limit - Abdul Taib, Luckman; Abdul Hadi, Muhammad Salihi; Umarov, Bakhram A. (IOP, 2018)
The existence of dark strongly localized modes of binary discrete media with cubic-quintic nonlinearity is numerically demonstrated by solving the relevant discrete nonlinear Schrödinger equations. In the model, the coupling coefficients between adjacent sites are set to be relatively small representing the anti-continuum limit. In addition, approximated analytical solutions for vectorial solitons with various topologies are derived. Stability analysis of the localized states was performed using the standard linearized eigenfrequency problem. The prediction from the stability analysis are furthermore verified by direct numerical integrations.